2017
DOI: 10.4212/cjhp.v70i4.1673
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-Based Pharmacy Practice?

Abstract: -

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Several studies reported barriers to utilization of current best evidence in daily pharmacy practice, including high clinical workload, and lack of basic skills and knowledge of critical appraisal [ 4 , 6 , 27 ]. Involving community pharmacists in PBR can potentially help break barriers to the utilization of the current best evidence in everyday pharmacy practice [ 3 , 10 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies reported barriers to utilization of current best evidence in daily pharmacy practice, including high clinical workload, and lack of basic skills and knowledge of critical appraisal [ 4 , 6 , 27 ]. Involving community pharmacists in PBR can potentially help break barriers to the utilization of the current best evidence in everyday pharmacy practice [ 3 , 10 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Current best evidence has been defined as “the best available external clinical evidence from clinically relevant research, often from basic sciences of medicine, but especially from patient centred clinical research” Current best evidence has been reported to overturn previously accepted measures in patient care such as diagnostic tests and treatments protocols and replaces them with the current safer and more efficacious options. The utilization of current best evidence in pharmacy practice, which is defined as the use of the best available evidence in clinical practice, is an essential component in the cycle of clinical interventions to improve the public’s health and help patients achieving their therapeutic goals [ 2 , 3 ]. In order to undergo clinically reasonable interventions and make practice decisions, pharmacists need to utilize the current scientific evidence from the literature [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation